STRATEGI REHABILITASI EKOSISTEM MANGROVE BERDASARKAN ANALISIS KESESUAIAN HABITAT DI KAWASAN PLTU BANTEN 3, LONTAR - Ahmad Fauzi; Fredinan Yulianda; Gatot Yulianto; Sulistiono Sulistiono; Fajar Adi Purnama (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Mangroves rehabilitation is needed for the recovery and development of mangrove ecosystems in area of coal power plant (PLTU) 3 of Banten, Lontar area that has been damaged and decreased its function. The success of a rehabilitation program is influenced by a mature rehabilitation planning strategy that takes into account ecological parameters. This study aimed to determine the suitability of habitat, the level of damage, and make recommendations for the rehabilitation of mangrove ecosystem in the Banten PLTU 3 Lontar area. This study was conducted in the mangrove rehabilitation area of coal power plant (PLTU) 3, Lontar, in January 2020. Retrieval of primary data through field observations using a spatial approach including quadrant transect methods in mangrove ecosystems, water quality aspects with insitu sampling and spatial analysis to determine habitat suitability based on geographic information systems. Mangroves conditions in coal power plant area Banten 3 Lontar area were at moderate and severely damaged levels. We found two types of mangrove i.e., Avicennia marina and Rhizophora mucronata. Mangrove rehabilitation area in area of coal power plant (PLTU) 3 had diurnal tidal type, sandy clay substrate, 2-5% C-organic content, 30-32 salinity ranges, and 7.3-7.5 pH distribution ranges. Mangrove ecosystem area in Banten PLTU 3 Lontar was 14.874 m2. Mangrove ecosystem rehabilitation in the area of coal power plant (PLTU) 3 of Banten can be conducted with four rehabilitation strategies such as adjusting and preparing habitat conditions, optimizing water flow, and replanting mangroves.